Photovoltaic limitations of FAPbI3 nanocrystal solar cells associated with ligand washing processes - Galatopoulos, Fedros; Papagiorgis, Paris; Ioakeimidis, Apostolos; Chrusou, Alexandra Z.; Souzou, A; Christodoulou, Constantinos; Bernasconi, Caterina; Bodnarchuk, Maryna I.; Leontidis, Epameinondas; Kovalenko, Maksym V.; Itskos, Grigorios; Choulis, Stelios A. (My University, 2024)
The processing of perovskite nanocrystals (PNCs) solar cells (SCs) usually incorporates ligand washing (LW) procedures. We show that a LW step of FAI in EtAc assists in the removal of the oleic acid/oleylamine ligands and improves the JSC and FF values of FAPbI3 based SCs. Although by increasing the exposure time of EtAc the removal of oleic acid/oleylamine ligands is more effective, sintering/necking of the FAPbI3 results to NC agglomerations and formation of defects/traps are observed within the active layer by the reported photoluminescence studies. Despite identifying the balanced in LW procedure exposure time, limitations on the performance of FAPbI3 PNCs SCs are reported. To identify the photovoltaic limitations impedance spectroscopy studies are presented and show that in the case of FAPbI3 PNC SCs an intermediate frequency response manifests. The observed impedance spectroscopy intermediate frequency response correlates with a parasitic resistance effect, indicating charge transport limitations and charge recombination losses even after the applied LW processing procedure
Keywords: Optoelectronic devices; Perovskite solar cell; Nanocrystals; Photovoltaics; Charge recombination; Charge transport; Electrochemical impedance spectroscopy; Solar cells; Photoluminescence spectroscopy; Ligands